Perlindungan Hukum bagi Konsumen dalam Transaksi Jual Beli Online atau e-Commerce menurut Undang-undang Nomor 8 Tahun 1999 dan Undang-undang Nomor 11 Tahun 2008 di Indonesia - Ismunandar, Arif; Indah Wulandari , Citra; Ma'ruf, Chasan (Journal Tafkirul Iqtishodiyyah, 2021)
The development of information and technology makes it easier for Indonesian people to get information and insight about products and goods needed in everyday life. One of the developments in technology and information is the internet media. Online buying and selling sites (e-commerce) are increasingly widespread today so that consumers are required to be careful in every online transaction. With legal guarantees and laws for consumers, it is hoped that there will be a legal basis in providing protection to consumers who transact e-commerce. This writing aims to find out whether legal rights as consumers, in the sense of legal protection for consumers, have been carried out properly and correctly, according to applicable laws. This research is a normative legal research. Where is the research on the principles and rules of law that guide the attitudes and behavior of the community. This research was conducted on the application of legal principles in legal protection for consumers related to the inclusion of problems that often occur in online buying and selling transactions between business actors and consumers. From the results of the discussion, it can be concluded that the UUPK and UU ITE have been able to provide adequate legal protection for consumers in buying and selling movable goods through e-commerce. regarding the use of consumer personal data, the legal requirements of an e-commerce transaction, the use of CA (Certification Authority), the issue of standard clauses and regulating actions that are prohibited for business actors in marketing and producing goods and services that can be used as a reference for objects in e-transactions. commerce.